SARS‐CoV‐2 and guttate psoriasis: A case report and review of literature - Elrazi Ali (14777284) (2023)
Guttate psoriasis is a rare dermatological presentation of SARS-CoV-2 infection and is seen mainly in patients with an underlying disease psoriasis. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4568